New records of and key to Tardigrada from Costa Rica - Kaczmarek, ŁUkasz (Zootaxa, 2003)
Moss samples collected near the research station “La Selva” on the edge of Costa Rican tropical rain forest has yielded three species of Tardigrada: Hypsibius pallidus Thulin, Astatumen trinacriae (Arcidiacono) and Macrobiotus polyopus Marcus. Another three unidentified species from the genus Macrobiotus were also found. All identified species are new for Costa Rica. A key to the identification of all known species from Costa Rica is given.